2018
DOI: 10.3389/fnhum.2018.00484
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Alterations in Electroencephalography Connectivity and Network Topology During n-Back Working Memory Task

Abstract: The study of the healthy brain in elders, especially age-associated alterations in cognition, is important to understand the deficits created by Alzheimer's disease (AD), which imposes a tremendous burden on individuals, families, and society. Although, the changes in synaptic connectivity and reorganization of brain networks that accompany aging are gradually becoming understood, little is known about how normal aging affects brain inter-regional synchronization and functional networks when items are held in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 70 publications
11
29
0
Order By: Relevance
“…The RT of the subjects was found positively correlated to FC in the alpha and beta bands, however only during the control state. In contrast, subject accuracy was found negatively correlated with FC in the beta and gamma bands, although only in the most challenging setting (3-back).Our results are in line with earlier reports on decreased connectivity during the n-back WM paradigm(Dai et al, 2017;Ginestet & Simmons, 2011;Hou et al, 2018). However, in contrast to Dai et al (2017), we found a stimulation-related decrease in E and C…”
supporting
confidence: 90%
See 4 more Smart Citations
“…The RT of the subjects was found positively correlated to FC in the alpha and beta bands, however only during the control state. In contrast, subject accuracy was found negatively correlated with FC in the beta and gamma bands, although only in the most challenging setting (3-back).Our results are in line with earlier reports on decreased connectivity during the n-back WM paradigm(Dai et al, 2017;Ginestet & Simmons, 2011;Hou et al, 2018). However, in contrast to Dai et al (2017), we found a stimulation-related decrease in E and C…”
supporting
confidence: 90%
“…Conversely, no effect of task difficulty on FC could be identified. in both the theta and alpha bands and in the beta band, respectively, while Hou et al (2018) found an increase in the same measures. These seemingly contradictory results may be attributed to differences in the analysis pipeline, which can affect results significantly even when obtained from the same dataset (Jalili, 2016;Lindquist, 2020).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations